Exploring Differences in the Lives and Well-Being of Sexual and Gender Minority Adults Experiencing Homelessness Relative to Their Cisgender Heterosexual Counterparts - Vanessa Schick; Laura Witte; Lourence Misedah; Wendy Benedict; Kinnon Falk; Carlie Brown; Frances Isbell (Mary Ann Liebert, 2019)
Purpose: To better understand the lives and experiences of sexual and gender minority (SGM) adults experiencing homelessness relative to their cisgender heterosexual (non-SGM) counterparts. Methods: A modified time-location sampling strategy was used to reach a diverse sample of individuals with experiences of homelessness. Interviewer or self-administered paper-based surveys were administered to participants on location. Results: SGM and non-SGM participants reported significant differences in the age at which they became homeless, their current housing, and experiences of violence over the past year. SGM participants reported poorer mental health than their non-SGM counterparts. Conclusion: SGM adults may be uniquely impacted by their experiences of homelessness.